PEMBERDAYAAN EKONOMI PARIWISATA BERBASIS MASYARAKAT MELALUI PENGOLAHAN SINGKONG MENJADI ANEKA CAMILAN - Idah Kusuma Dewi; Sri Yuwanti; Ahmad Mansur; Laksono Hujianto (Jurnal Pengabdian Masyarakat Waradin, 2021)
The food consumption diversification program for the people of Kwadungan Village is the basis for community-based tourism economic empowerment activities that process cassava plants into various selling-worthy snacks to tourists. The problem faced is the lack of knowledge on how to make cassava based snacks. The community service model is to directly involve groups of women tobacco farmers in utilizing the potential of local agricultural plants to become a typical culinary product of Kwadungan Village. The results of the activity were various snack products from the training of cassava processing such as cassava sticks, cassava croquettes, cassava klapertaart and cassava pastels made by women from tobacco farming groups.